Comparative study of wife's employment in jurisprudence and legal system of Iran and Egypt and its effect on Islamic lifestyle - Sarmadi, Seyed Ali; Ghanbarpor, Behnam; Gholami, Jahanbakhsh (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this research was to compare and contrast the dowry and alimony of women in the Islamic and Western legal systems. Method: This study was conducted in a descriptive-analytical manner using library sources. Texts in the form of books and articles in Persian and English as well as newspapers were used in this way. In addition, reputable internet search engines such as Google and Yahoo were used in the development of this research. Results: In this study, the financial rights of husband and wife towards each other, financial independence of couples, and laws related to dowry and alimony were examined in Islam and the West. Conclusion: The Islamic legal system, according to the five schools of jurisprudence, has special financial privileges for the wife, which is almost unique compared to Western legal systems. One of these privileges is "dowry." Dowry is a mandatory gift that belongs to the wife and although it is not a condition for the validity of marriage, it becomes the responsibility of the husband as soon as the marriage contract is concluded, at least to the amount of the mahr al-mithl. Dowry is one of the financial rights of women in the Islamic family legal system. The judicial system of England and Wales is one of the most famous judicial systems in resolving divorce cases and observing equal rights for men and women, to the extent that London is called the divorce capital of the world. In the courts of this country, the man is considered as the main pillar of the family, but in case of divorce, the assets of both parties, and even their future retirement rights, will be examined and based on these examinations, excess assets beyond the needs of each party will be identified and divided equally between the wife and husband. This process is similar in most European and American countries, although structural differences in the law and judicial system of each country may lead to changes in the implementation of court orders.